Inovasi Alat Supervisi sebagai Solusi Pembinaan Pendidikan yang Efektif dan Berkelanjutan - Denis Bahari; Muhammad Ilmi Najib; Fitdarus Kussuma (Student Research Journal, 2024)
Innovation in supervision tools can improve the quality of education by providing constructive feedback, thus creating a better learning atmosphere; however, the success of its implementation is highly dependent on the support of all parties involved, such as teachers, parents, and the community. The purpose of this study is for researchers to provide a solution for Innovation in supervision tools for effective and sustainable educational development. The object of research is Innovation in supervision tools as a solution for effective and sustainable educational development at SMP Plus Darussalam. This study uses a qualitative research type with a case study approach. This study uses a qualitative research type with a case study approach, which allows researchers to explore in detail the phenomenon of innovation in supervision tools at SMP Plus Darussalam. The sources of informants in this study were the principal, teachers and students of SMP Plus Darussalam Blokagung. Data collection techniques in this study were observation, interviews, and documents. The results of this study Innovation in supervision tools as a solution for effective and sustainable educational development produced findings including research on innovation in supervision tools as a solution for effective and sustainable educational development resulting in Competency-Based Supervision Modules, Integrated Feedback Systems, and Stakeholder Involvement.